Pentingnya Peran Orangtua Dalam Mencegah Permasalahan Perilaku Sosial AUD - Manzilatul Fathy; Rifasya Nurfadillah; Purwati Purwati; Sima Mulyadi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2023)
In the social development of children, children's social development is very important in living in society with other people, therefore in socializing in their community children must have good social behavior without any unsocial behavior. The purpose of this study was to describe the important role of parents in preventing AUD social behavior problems. This research uses the method of library research (library research). The results of this study concluded that the role of parents is very important in stimulating the development of social behavior, children print parental behavior at home because children are reliable imitators, the importance of the role of parents in implementing parenting and habituation, religious norms and values ​​in an effort to prevent social behavior problems in children. As parents who want their children to have good social behavior, parents must be able to apply parenting/educational methods and use good habituation methods regarding norms and religion while at home.